The Constitution of Kenya: Contemporary Readings - Lumumba, P.l.o; Lumumba, P.l.o; Mbondenyi, Kiwinda (LawAfrica Publishing Ltd, 2011)
The Constitution of Kenya: Contemporary Reading, provides an in-depth assessment of the interface between constitutionalism and Kenya$1 (Bs new Constitution. Focusing on the historical trajectory on the search for a new Constitution, Chapter One lays the groundwork upon which the fault line between constitutionalism and the issue areas are articulated in the other chapters in relation to the new Constitution. The superb chapters on the carefully selected issue areas, make this edited volume an essential reading. The book makes an important contribution to the evolving constitutionalism and policy clarification on Kenya$1 (Bs new Constitution. It is a welcome and timely intervention by legal scholars and practitioners on the new constitution and the challenges facing Kenya in its implementation. The book is an excellent teaching and reading manual for students in law, history, politics, diplomacy, and international relations as well as for the practitioners.s